Методи визначення та усунення можливих відхилень частоти в роботі об'єднаних енергосистем за раптового порушення балансу потужностей - Dubovskoy S.V.; Lenchevsky Ye.A.; Tuwarshiew W.K. (General Energy Institute of the National Academy of Sciences of Ukraine, 2006)
The questions of problems related to the methods of determination and analysis of frequency rejection values on the example of one sudden disconnecting of powerful power units from Ukrainian UPS are considered. The proper researches are conducted and the graphs of calculation area of frequency rejections are built from its basic value. It is grounded, that at violations of the system operation modes to remove the rejections of frequency are possible more expediently by the speed regulators and automatic frequency regulators instead of introduction of additional powers.